The Application of Head-Up Tilt Test to Diagnose Hemodynamic Type of Orthostatic Intolerance in Children Aged Between 3 and 5 Years - Zou, Runmei; Wang, Shuo; Li, Fang; Lin, Ping; Zhang, Juan; Wang, Yuwen; Xu, Yi; Wang, Cheng (Frontiers in Pediatrics, 2021)
Objectives: Head-up tilt test (HUTT) is a useful tool to assess autonomic function and reproduce neurally mediated reflex. In this present study, we evaluated the use of HUTT in pediatric patients aged 3 to 5 years old with orthostatic intolerance. Materials and Methods: The medical history and HUTT records of 345 (180 males, aged from 3 to 5 years old) cases of patients who complained symptom of orthostatic intolerance and visited Syncope Ward, Children’s Medical Center, the Second Xiangya Hospital, Central South University from January 2003 to December 2019 were retrospectively reviewed. Results: 79 (22.9%) cases had positive responses to complete HUTT (basic HUTT and sublingual nitroglycerin HUTT), while 29 (8.4%) cases had positive responses if only basic HUTT was performed. Sublingual nitroglycerin provocation significantly increased the positive rate of the test (x2=27.565, P＜0.001).The most frequent hemodynamic response to HUTT was vasoinhibitory type vasovagal syncope (12.2%). Syncope (28.7%) and dizziness (22.6%) were the most common symptoms. 8 cases discontinued the test due to intolerable symptoms without severe adverse events occurring. Conclusions: HUTT was safe and well tolerated, and could be used to diagnose hemodynamic type of orthostatic intolerance in children aged 3 to 5 years old.